The Competition Between ISPs in Presence of the Net Neutrality - Mohamed El Amrani; Hamid Garmani; Mohamed Baslam; Rachid El Ayachi (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
In this work, we present an economic model of computer networks that describes the in-teraction between Internet Service Providers (ISP ), customers and content provider. The competition between ISP s may be translated by the prices they require and the qualities of service (QoS) they offer. The customer demand for service from an ISP does not only de-pend on the price and quality of service (QoS) of the ISP , but it is influenced by all those offered by its competitors. This behavior has been extensively analyzed using game the-ory as a decision support tool. We interpret a non-neutral network when a content provider privileges ISP s by offering them more bandwidth to ensure proper QoS to support ap-plications that require more data transport capacity (voice over internet protocol (V OIP ) the live video streaming, online gaming). In addition, our work focuses on the price game analysis and QoS between ISP s in two cases: neutral network and non-neutral network. After showing the existence and uniqueness of equilibrium in terms of quality of service, we analyzed the impact of net neutrality on competition between ISP s. We also validated our theoretical study with numerical results, which show that the game has an equilibrium point which depends on all the parameters of the system.